2016
DOI: 10.1242/jeb.136259
|View full text |Cite
|
Sign up to set email alerts
|

Control of lung ventilation following overwintering conditions in bullfrogs,Lithobates catesbeianus

Abstract: Ranid frogs in northern latitudes survive winter at cold temperatures in aquatic habitats often completely covered by ice. Cold-submerged frogs survive aerobically for several months relying exclusively on cutaneous gas exchange while maintaining temperature-specific acidbase balance. Depending on the overwintering hibernaculum, frogs in northern latitudes could spend several months without access to air, the need to breathe or the chemosensory drive to use neuromuscular processes that regulate and enable pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 72 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…This strongly implies that phenotypic plasticity decreases CO 2 /pH sensitivity in response to aquatic overwintering by acting on chemosensory mechanisms (be they intrinsic or extrinsic to the neuron) and not general dysfunction of neurons in the respiratory control network. Collectively, these data indicate that aquatic overwintering conditions lead to a (at least temporary) reduction of ventilatory (Santin & Hartzler, a ) and central (Figs ) CO 2 chemosensitivity, at least in part, by decreasing CO 2 ‐induced firing responses of presumed respiratory control neurons (Figs and ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…This strongly implies that phenotypic plasticity decreases CO 2 /pH sensitivity in response to aquatic overwintering by acting on chemosensory mechanisms (be they intrinsic or extrinsic to the neuron) and not general dysfunction of neurons in the respiratory control network. Collectively, these data indicate that aquatic overwintering conditions lead to a (at least temporary) reduction of ventilatory (Santin & Hartzler, a ) and central (Figs ) CO 2 chemosensitivity, at least in part, by decreasing CO 2 ‐induced firing responses of presumed respiratory control neurons (Figs and ).…”
Section: Discussionmentioning
confidence: 77%
“…Several lines of evidence suggest that mechanisms underlying CO 2 chemosensitivity of lung breathing are reduced following overwintering. First, ventilatory responses to CO 2 challenge are reduced following aquatic overwintering in vivo through inability to increase breathing frequency (Santin & Hartzler, a ). Second, although we showed that aquatic overwintered bullfrogs had a higher baseline lung frequency, reduced brainstem chemosensitivity was unlikely to have occurred as a result of a ‘ceiling effect’.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, once frogs emerge from 2 to 3 months in this environment simulated in the lab, they breathe normally to match their resting metabolic demands at a warm body temperature (Figure 1b). In addition, the motor system retains a sufficient scope to increase beyond baseline during hypoxic challenge, a common respiratory stimulant (Figure 1c; Santin & Hartzler, ). These results show that frogs maintain the capacity for a range of breathing outputs despite the complete absence of rhythmic motor function for several months.…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 99%